PENGARUH MEDIA KUNANG-KUNANG HITUNG (FIREFLY MATH) TERHADAP KEMAMPUAN BERHITUNG PESERTA DIDIK KELAS 2 SEKOLAH DASAR - Siti Nurhalizah; Muhammad Sofwan; Violita Zahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to find out the effect of the use of Firefly Math Media on the arithmetic skill of second-grade students at SD Negeri 55/I Sridadi. The research design used a quantitative approach involving two classes, namely class 2D as the experimental class (13 students) and class 2C as the control class (17 students). Data were collected through pre-test and post-test, then analyzed using the SPSS 29 program. The results of the descriptive analysis showed that the average pre-test scores of both groups were relatively comparable (42,85 and 44,13). After treatment, the average score of the experimental class increased to 58,31, while the control class was 53,00, with a difference of 5,31 points. The normality and homogeneity assumption tests showed that the data were normally distributed and homogeneous. Analysis using Mixed Design ANOVA showed that the time factor had a significant effect on students' scores. Thus, it can be concluded that the use of Firefly Math Media is effective in improving students' arithmetic ability.